2019
DOI: 10.1080/21645515.2018.1564434
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in uptake of 13-valent pneumococcal conjugate vaccine among older adults in the United States

Abstract: Background : In September 2014, 13-valent pneumococcal conjugate vaccine (PCV13) was universally recommended for all US adults aged ≥65 years. Adult PCV13 coverage, including whether disparities in uptake exist, however, is not well-described. Methods : We used a monthly series of cross-sectional analyses of administrative medical and prescription claims data collected by IQVIA and linked to sociodemographic data collected by Experian to estimate overall and subpopulation-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 38 publications
8
25
0
1
Order By: Relevance
“…Knowledge, information in mass media, access to consultation and prescriptions, should be reviewed as barriers in achieving greater vaccination rates in this vulnerable cohort. During the COVID-19 pandemic, this inequity in access to healthcare was more visible, according to several studies [ 57 , 58 , 59 , 60 , 61 ]. Even more, global gross domestic product shrinkage of 3.2% in 2020 was predicted by the United Nations, and that will push 34 million more people into extreme poverty [ 62 ] with a potentially worse scenario for IV and PV rates for the next years if proper measures are not taken by stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge, information in mass media, access to consultation and prescriptions, should be reviewed as barriers in achieving greater vaccination rates in this vulnerable cohort. During the COVID-19 pandemic, this inequity in access to healthcare was more visible, according to several studies [ 57 , 58 , 59 , 60 , 61 ]. Even more, global gross domestic product shrinkage of 3.2% in 2020 was predicted by the United Nations, and that will push 34 million more people into extreme poverty [ 62 ] with a potentially worse scenario for IV and PV rates for the next years if proper measures are not taken by stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…[ 100,101 ] Pneumococcal vaccination rates among adults over 65 varied from 18% to 91% both within neighborhoods in individual cities such as Chicago [ 102 ] and nationally as a function of the same factors. [ 103 ] Geographical locations with the lowest vaccination rates invariably have the highest rates of COVID‐19 cases.…”
Section: Evidence For the Hypothesesmentioning
confidence: 99%
“…Higher acceptance was found among women than men and by those aged at least 65 years old. Another study performed in the USA, limited to the population of adults aged 65 or above, revealed that the uptake of the pneumococcal vaccine was lower among: those of black and Hispanic ethnicity, than among non-Hispanic whites; by the poor rather than those with the highest income; among those with a low level of education than among those with at least college education and finally among those living in rural communities or urban inner-city areas, rather than those living in suburban areas [34].…”
Section: Discussionmentioning
confidence: 99%